CALL Design: Principles and Practice - Proceedings of the 2014 EUROCALL Conference, Groningen, the Netherlands 2014
DOI: 10.14705/rpnet.2014.000253
|View full text |Cite
|
Sign up to set email alerts
|

Context-aware writing support for SNS: Connecting formal and informal learning

Abstract: This paper presents another stage in a series of research efforts by the authors to develop an experience-connected mobile language learning environment, bridging formal and informal learning. Building on a study in which the authors tried to connect classroom learning (of German in Japan) with learners' real life experiences abroad by having smartphones detect the learners' location and supply them with multimedia content matching their real-time communicative situation, the authors developed a hybrid languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…However, it has to be admitted that the students' posts did not purely derive from an authentic desire to socialise or to share information, but were a requirement of their language class. In this regard, it has to be further investigated how differences between students' private and teacher-assigned SNS interactions affect L2 learning (Leier & Cunningham, 2016;Waragai et al, 2014). In their more learner-centred approach, Promnitz-Hayashi (2013) let students design their own tasks, which significantly increased the number of prompted comments as compared to teacher-assigned tasks.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has to be admitted that the students' posts did not purely derive from an authentic desire to socialise or to share information, but were a requirement of their language class. In this regard, it has to be further investigated how differences between students' private and teacher-assigned SNS interactions affect L2 learning (Leier & Cunningham, 2016;Waragai et al, 2014). In their more learner-centred approach, Promnitz-Hayashi (2013) let students design their own tasks, which significantly increased the number of prompted comments as compared to teacher-assigned tasks.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As for GFL students in Japan, Waragai et al (2014) found that learners make more use of the L2 within private messaging than within assigned activities for concerns of formal adequacy. Clearly, more research is needed on both students' private usage as well as study-related SNS use in order to arrive at an understanding of how learners might be assisted best in their endeavour to utilise such technologies for their L2 learning.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study is carried out before the long-term background of our continuous experiments. At the Keio University Shonan Fujisawa Campus (Japan), researchers and educators have been working on designing computer-based language learning environments to provide language learners (mainly of German) with learning opportunities outside the classroom that are linked to classroom content (Waragai, Ohta, Raindl, & Kurabayashi, 2013;Waragai et al, 2014). This paper is focused especially on writing activity in a foreign language.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have been exploring different ways of connecting places in German speaking countries and classroom learning contents, by designing MLLEs that supplied learners with learning materials according to (1) situations experienced in specific places (in public transport, in restaurants, etc. ), offering on-the-spot help for oral interaction (Waragai, Ohta, Raindl, & Kurabayashi, 2013), or (2) the places that learners had visited during the day, providing them with scaffolding for writing SNS-entries about their experiences (Waragai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%